Sitti Sutinah Suhardi's Political Communication Strategy in Defeating the Incumbent in the 2020 Mamuju Regional Elections - Basir, Muhammad Fausan; Sukmarini, Andi Vita; Djalil, Nur Alim (Journal Social Civilecial, 2026)
This study aims to analyze the political communication strategy employed by Sitti Sutinah Suhardi in defeating the incumbent candidate in the 2020 Regional Head Election (Pilkada) of Mamuju Regency, Indonesia. The study is motivated by the phenomenon in which a challenger candidate with relatively lower initial popularity and electability was able to overcome the structural advantages typically possessed by an incumbent. This condition indicates that political communication strategies play a crucial role in shaping public political preferences in local electoral contests. This research adopts a qualitative approach using a case study method. Data were collected through in-depth interviews with key informants involved in the campaign process, observations, and documentation related to political communication activities during the campaign period. The theoretical framework applied in this study includes Aristotle’s rhetorical theory ethos, pathos, and logos as well as Nimmo’s political communication model that emphasizes the interaction between political actors, political media, and political publics. The findings reveal that Sitti Sutinah Suhardi’s political communication strategy was implemented through three main stages: planning, implementation, and evaluation. This study concludes that the success of a challenger candidate in defeating an incumbent is not solely determined by political resources or structural advantages, but also by the ability to design and implement effective, adaptive, and context-sensitive political communication strategies.